How smallholder dairy systems in Kenya contribute to food security and poverty alleviation: results of recent collaborative studies - Muriuki, H.G.; Mwangi, David Miano; Thorpe, W.R. (International Livestock Research Institute, 2001)
Kenya has the largest dairy sub-sector in eastern and southern Africa making available annually an estimated 85-90 litres of liquid milk equivalent per capita based primarily upon well-established market-oriented smallholder dairy systems. As a result dairying (the production of milk for the market) has become a very significant source of income and food for an estimated 625,000 smallholder producer households and for those involved in the marketing of milk, in total some 25% of all households. In addition dairying plays a crucial role in sustaining smallholder crop-dairy systems through its contributions to nutrient cycling. It is these smallholder crop-dairy systems, generally based on the cropping of the staple food, maize, that dominate marketed dairy production and that underpin the competitiveness of smallholder dairying in Kenya.